Absolute and relative sea-level rise in the New York City area by measurements from tide gauges and satellite global positioning system - Alberto Boretti (Journal of Ocean Engineering and Science, 2021)
The absolute and relative rates of rise of the sea level are computed for the New York City area by coupling global positioning system records of the position of fixed domes nearby tide gauges, with the tide gauges’ records. Two tide gauges are considered, one long-term trend, more reliable, The Battery, in lower Manhattan, and one shorter, less reliable, Sandy Hook, in New Jersey. The relative rates of rise of the sea level are +2.851 and +4.076 mm/yr. The subsidence rates are -2.151 and -3.076 mm/yr. The absolute rates of rise of the sea level are +0.7 and +1.0 mm/yr. The relative sea-level acceleration, reliable only in The Battery, is about +0.008 mm/yr². This acceleration is about the same as the world average long-term trend tide gauge, as well as the average long-term trend tide gauge of the East Coast of North America. The absolute rate of rise of the sea level by 2050 in the lower Manhattan area will be likely less than 30 mm, and the absolute rate of rise of the sea level by 2100 likely less than 80 mm. The relative rate of rise of the sea level by 2050 in the Manhattan area will be likely 85 mm, and the relative rate of rise of the sea level by 2100 likely 228 mm, because of the overwhelming subsidence contribution.